PERANCANGAN MODEL PENGUKURAN KINERJA CORPORATE SOCIAL RESPONSIBILITY PADA PENGEMBANGAN BISNIS UKM PADA PT.YTL JAWA TIMUR - Nurmianto, Eko; Wessiani, Naning Aranti; Munawaroh, Maidatul (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2012)
Sustainable CSR in SME business development within industry is as an important challenge which could not be postponed. Performance measurement method of Performance Prism used to measure the Performance of CSR on SME business development at PT.YTL Jawa Timur. Performance Prism is one of an integrated methods which consist of all aspects,i.e; stakeholder satisfaction, contribution, strategy, process and capability. Performance measurement design is also supported by several method such as Analytic Hierarchy Process (AHP), scoring system with Objective Matrix (OMAX) and Traffic Light System (TLS). The design of CSR Performance measurement in SME business development at PT YTL Jawa Timur with Performance Prism resulted in 37 key Performance indicator (KPI), among others 13 KPI on stakeholder community, 10 KPI on stakeholder KLUCIL, 8 KPI on stakeholder instructur and 6 KPI on stakeholder regulator. From the calculating of Performance measurement using OMAX represent that Performance of CSR in SME business development is 6.72 which means that CSR Performance on SME business development has not optimal yet.